Translational Studies in Hematopoietic Cell Transplantation: Treatment of Hematologic Malignancies as a Stepping Stone to Tolerance Induction - Strober, Samuel (2011)
Allogeneic hematopoietic cell transplantation (HCT) has most commonly been used to treat hematologic malignancies, where it is often the only potentially curative option available. The success of HCT has been limited by transplant-associated toxicities related to the conditioning regimens used and to the common immunologic consequence of donor T cell recognition of recipient alloantigens, graft-vs-host disease (GVHD). The frequency and severity of GVHD observed when extensive HLA barriers are transgressed has essentially precluded the routine use of extensively HLA-mismatched HCT. Allogeneic HCT also has potential as an approach to organ allograft tolerance induction, but this potential has not been previously realized because of the toxicity associated with traditional conditioning. In this paper we review two approaches to HCT involving reduced intensity conditioning regimens that have been associated with improvements in safety in patients with hematologic malignancies, even in the HLA-mismatched transplant setting. These strategies have been applied in the first successful pilot studies for the induction of organ allograft tolerance in humans. Thus, we summarize an example of vertical translational research between animal models and humans and horizontal translation between two separate goals that culminated in the use of HCT to achieve allograft tolerance in humans.